Influence of social support on asthma self-management in adolescents. (4th March 2021) - Sloand, Elizabeth; Butz, Arlene; Rhee, Hyekyun; Walters, Leanne; Breuninger, Kathleen; Pozzo, Rosario Alejandra; Barnes, Christina Marie; Wicks, Mona Newsome; Tumiel-Berhalter, Laurene
Abstract: Objective: Adolescents with asthma are influenced by peers and family. The objective was to better understand family social support and test its association with medication adherence, asthma control, and Emergency Department (ED) use. Methods: This study is a cross-sectional secondary data analysis from a randomized controlled trial with urban adolescents from three U.S. cities. Participants (12-20 years old) with asthma completed the Perceived Family Support Scale (PFS) and Horne's Medication Adherence Report Scale (MARS). Data from both tools were classified into 2 categories- high and low (< 25 th percentile) perceived family support and high (total score >10) and low medication adherence, respectively. Chi-square statistic and logistic regression were used for analysis. Results: Of the 371 participants, the majority were young (96% ≤ 17 years), African American or Bi-racial (85%), and Medicaid-insured (72%); over one-third had maternal family history of asthma. Among those on a controller medication ( n = 270), only 37% reported its use ≥8 days over 2 weeks. Asthma control was poor with 50% categorized "not well controlled, " 34% "very poorly controlled." Participants responded positively to most social support items. One item, providing and receiving social support to and from family members, was less often positively reported. Low medication adherence was significantly associated with lower perceived social support ( p = 0.018). Conclusion: This study underscores the importance of family social support in understanding the extent of adolescents' self-management, particularly medication adherence.